Microbiological and Compositional Characteristics of Çeçil Cheese Collected from Households in Erzurum, Turkey - DIKBAS†, NESLIHAN; SENGÜL*, MUSTAFA; FATIH ERTUGAY, M. (Asian Journal of Chemistry, 2024)
The objective of this work is to determine the microbiological and chemical characteristics of Çeçil cheese. A total of 15 samples of Çeçil cheese were collected from individual households in Erzurum, Turkey. In the samples, average of total aerobic mesophilic bacteria, yeast and moulds, lactic acid bacteria (LAB) and Staphylococcus aures were determined to be 1.6 × 106, 7.0 × 104, 1.8 × 105, 6.4 × 102 cfu/g, respectively. Coliform bacteria were lower than < 10 cfu/g in 86.66 % of the samples. On the other hand, the coliform positive samples showed an average of 8.5 × 101 cfu/g. S. aureus were not detected in 46.66 % of Çeçil cheese samples. One hundred and eighteen strains of lactic acid bacteria isolated from Çeçil cheese were identified. Three genera were found: Lactobacillus (88.13 %), Leuconostoc (5.93 %) and Pediococcus (5.93 %). Lactic acid bacteria dominated the microflora of these samples, especially the genera Lactobacillus. The dominant Lactobacillus species were Lb. coryniformis subsp. coryniformis (36 strains), Lb. brevis (29 strains). In Çeçil cheese samples analyzed, dry matter, fat, salt, total nitrogen, pH, titratable acidity and ash values were found between 34.80 and 59.30 g/100 g cheese, 2.0 and 14.0 g/100 g cheese, 5.49 and 15.09 g/100 g cheese, 13.40 and 31.70 g/100 g cheese, 5.35 and 4.92, 0.32 and 1.05 %, 9.37 and 18.50 g/100 g cheese, respectively.